ELASTIC MEMBRANE DEFORMATIONS GOVERN INTERLEAFLET COUPLING OF LIPID-ORDERED DOMAINS - Galimzyanov, Timur R. (Phys Rev Lett, 2015)
The mechanism responsible for domain registration in two membrane leaflets has thus far remained enigmatic. Using continuum elasticity theory, we show that minimum line tension is achieved along the rim between thicker (ordered) and thinner (disordered) domains by shifting the rims in opposing leaflets by a few nanometers relative to each other. Increasing surface tension yields an increase in line tension, resulting in larger domains. Because domain registration is driven by lipid deformation energy, it does not require special lipid components nor interactions at the membrane midplane.